Peran Pengalaman Kerja Karyawan pada UMKM Mille Crepes Sinok Karawang - Asyifa, Asyifa; Gunawan, Dinar Mustika; Sandi, Santi Pertiwi Hari; Hidayaty, Dwi Epty (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Excellent human resources are highly needed in businesses or companies to achieve organizational or activity goals. The purpose of this observation is to determine the role of work experience in creating employee performance quality. The methods used are interviews, observations, and literature reviews. To achieve their goals and efforts, UMKM actors need experienced human resources. Mille Crepes Sinok Karawang is an UMKM that sells food, and this business requires employees who are skilled in cooking. If an employee has insufficient experience in their field, their work quality will be low and will impact the progress of the business, making it unproductive. The result of this observation is that if employees have work experience in their field, it will create good employee performance quality, knowledge, skills or mastery of the job, and a sense of responsibility, so the business does not stop because employees have previous experience, creating good performance quality and producing appropriate products.